Enhancing Patient Outcomes in Maternal and Child Healthcare: The Role of Practitioners, OB-GYNs, Pediatricians, Nurses, and Midwives - Yazeed Hassn Althoweby, Thamer Eid Alhathla1 Abdullah Ali Alghamdi, Dr. Lubaid Al-Ghaithi, ‏ Jamila Ibrahim Al Mowalad, Dr. Taghreed Hamza Basri; Zainab Saleem Alhugail, Ohud Rasheed Almutairi, Shaikah Ahmed Alkhibari, Naseem Hamzah Ibrahim, Yousra Nasser Salih Altamimi, Samiah Saad Alshehri (Journal of International Crisis and Risk Communication Research, 2024)
Introduction: Prenatal and infant care is at the top of worldwide healthcare agendas, proving a focal aspect of the Well-Being Index. They refer to the medical needs of women before, during and after child birth as well as the medical needs of infants and children. This paper posits that delivery and early childhood health issues involve a combination of biological, environmental, and socio-economic factors that necessitates an integrated model for advancing the health of women and children and subsequently acing up the survival rates of the later. Aim of work: To explore the multifaceted contributions of OB-GYNs, pediatricians, nurses, and midwives to maternal and child healthcare. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Enhancing, Patient Outcomes, Maternal, Child Healthcare, Role, Practitioners, OB-GYNs, Pediatricians, Nurses, and Midwives. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Improving outcomes of patients in maternal and child health call for the use of multiple professionals such as OB-GYNs, pediatricians nurses, midwives among others with their unique perspectives. As such, creating partnerships and using the biological, psychosocial and environmental model, these practitioners can transform the health of mothers and children for the better. With an understanding that health care has issues of disparities, chronic illnesses and mental health among other issues, the future of advancing towards enhanced solutions to the pressing issues will indeed demand parallel qualities of enhanced fruitful interprofessional relations and patient-centered equities. Ideally, there are evidently emerging trends in approaches to the vaccine delivery system such as digital technologies, community-based model, and education to the providers. For this reason, therefore, societies should be encouraged to invest early in maternal and child health to ensure that the future is created to cater for the future generations.